Form follows Zero Energy: Technological Design for Sustainable Housing in Extreme Climate Areas - Antonio, Di Sivo Michele Basti; Daniela, Ladiana; Cristiana, Cellucci (Journal of Technology Innovations in Renewable Energy, 2018)
Hot and humid Extreme Climate Areas, like the United Arab Emirates, pose unique challenges for architects and engineers seeking innovative technologies for energy and environmental efficient building designs; at the same time, these regions are characterized by an innovative spirit that pushes to develop and implement projects to test renewable building technologies and solutions. The research team, which includes the Engineering faculty of The British University in Dubai, is working to develop design strategies that contribute to implementing low-energy and off-grid architecture in the UAE. The goal is to design a home balancing human comfort and efficient energy use, and to respond to the site’s climatic and contextual variables. The research aims to design a water-conserving, net-zero energy single-family home that can be used as a prototype for new building developments in this area. The approach developed toward an energy-efficient design process includes both traditional bioclimatic elements and high-performance active technological systems. The experimental design process also aims to reduce the building’s environmental impact while creating a comfortable and responsive living environment. In this way, efficient water use and renewable energy features can be aesthetically, economically and culturally integrated into the home’s architecture to improve its residents’ quality of life. The house design responds to the climate challenges and complements active systems reducing energy use and associated carbon emissions. At the same time, it aims to contribute to the development of appropriate architecture, a starting point for simple architectural expression in the UAE.